Relaxamento com visualização guiada: efeito sobre a fadiga e qualidade de vida relacionada à saúde de mulheres com câncer de mama em tratamento radioterápico - Siqueira, Lais Reis (2020)
Breast cancer occupies one of the first positions of malignant neoplasms in women. Among the types of treatment for such cancer is radiotherapy. Although it is a safe method, it has several side effects that impair health-related quality of life, with fatigue being one of the most debilitating and recurrent symptoms. Integrative and complementary practices are widely used in patients with cancer, among these, relaxation with assisted visualization, performed in order to reduce side effects. The present study has aimed at evaluating the effectiveness of the Relaxation with Assisted Visualization intervention, in reducing fatigue and improving health-related quality of life of women with breast cancer undergoing radiotherapy. Quantitative, quasi-experimental research, without a control group, with pre and post-test types, has been carried out with 25 women with breast cancer undergoing radiotherapy treatment. The practice of relaxation with assisted visualization consists of an audio recording containing verbal commands, so as to guide the patient to carry out the practice, performed by the study researcher individually, in a quiet environment, three times a week during the entire radiotherapy treatment. The therapeutic sociodemographic and clinical questionnaires at the beginning of treatment and the Health Related Quality of Life instrument (EORTC QLQ-C30) and the Revised Piper Fatigue Scale had been done at the beginning, in the middle and at the end of the treatment. For the Piper-Revised scale, a classification has been made in accordance with the ordinal categories and the t-test for comparison amongst the 1st (T1), the 2nd (T2) and the 3rd evaluations (T3). The Wilcoxon test has been used for the variables of the EORTC QLC-C30 tool and for the assessment of physiological parameters, comparing the three instances. For the association of sociodemographic and therapeutic clinical variables with the EORTC QLQ-C30 tool and the Piper-Revised Fatigue scale, the Kruskal Wallis and Mann Whitney tests have been used. Most patients were aged 41-60 years, with a good level of education, retired, catholic, white, married, in IIA staging. A reduction in the intensity of fatigue has been shown in all dimensions: behavioral, affective and sensory/ psychological. The EORTC QLC-C30 scores related to the functional scales have presented improvement throughout the treatment. The prevalent symptoms for the symptom scale were insomnia, constipation and fatigue. The physiological parameters have shown a reduction in the values among the evaluations, indicating a physiological relaxation after the relaxing sessions. Being a younger woman, having undergone chemotherapy and the number of chemotherapy sessions, are associated with a higher level of fatigue and worse scores for health-related quality of life. Relaxation with visualization is a low-cost complementary practice because it uses few technological resources with a low occurrence of side effects, and it can be performed by trained professionals, favoring the professional-nurse bonding. Thus, the present research has contributed to the advancement of the knowledge in the area of Integrative and Complementary Practices in Oncology, providing evidence of their effectiveness in reducing fatigue and improving the HRQoL of women with breast câncer undergoing radiotherapy.